Prenatal Breast Accupressure Efektif Mempercepat Waktu Pengeluaran ASI dan Meningkatkan Kecukupan ASI bagi Bayi - Triana Septianti Purwanto; Feby Angzila Fatmayati (FORIKES, 2023)
Prenatal breast accupresure is an effective complementary technique to accelerate the production of breast milk with an adequate amount of production, so as to increase the adequacy of breast milk for babies. The purpose of this study was to determine the effectiveness of prenatal breast accupressure in accelerating the production of breast milk and increasing its adequacy for the baby. The design of this study was a posttest only with control group, which involved 60 mothers in Magetan Regency, from the third trimester of pregnancy to the postpartum period. The sample was selected by systematic random sampling technique, which was divided into an intervention group and a control group, each consisting of 30 people. Measurements were measured through observation and interviews for the time of expressing breast milk, measuring baby's weight, calculating baby's weight gain, and adequacy of breast milk for babies. The p value of the results of statistical analysis was less than 0.05. It was concluded that prenatal breast acupressure was proven to be effective in accelerating the time for expulsion of breast milk and increasing the adequacy of breast milk for babies, and increasing baby's weight.Keywords: prenatal breast acupressure; expenditure; breast milk ABSTRAK Prenatal breast accupresure adalah teknik komplementer yang efektif untuk mempercepat pengeluaran air susu ibu dengan jumlah produksi yang adekuat, sehingga dapat meningkatkan kecukupan air susu ibu bagi bayi. Tujuan penelitian ini adalah mengetahui efektifitas prenatal breast accupressure untuk mempercepat pengeluaran air susu ibu dan meningkatkan kecukupannya bagi bayi. Rancangan penelitian ini adalah posttest only with control group, yang melibatkan 60 ibu di Kabupaten Magetan, sejak hamil trimester III hingga masa postpartum. Sampel dipilih dengan teknik systematic random sampling, yang dibagi menjadi kelompok intervensi dan kelompok kontrol, masing-masing terdiri atas 30 orang. Pengukuran diukur melalui observasi dan wawancara untuk waktu pengeluaran air susu ibu, pengukuran berat badan bayi, perhitungan kenaikan berat badan bayi, dan kecukupan air susu ibu bagi bayi. Nilai p dari hasil analisis statistik adalah kurang dari 0,05. Disimpulkan bahwa prenatal breast acupressure terbukti efektif untuk mempercepat waktu pengeluaran air susu ibu dan meningkatkan kecukupan air susu ibu bagi bayi, dan meningkatkan berat badan bayi.Kata kunci: prenatal breast acupressure; pengeluaran; air susu ibu